Development of an Inclusive Economic Education Program Based on Sustainable Management to Improve the Financial Resilience of Urban Families in Makassar - Iriani, Nisma; Ismail, Ismail; Kurnia, Ady; Utomo, Jepri; Mutmainnah, Inayatul; Ibadurrahman, Ibadurrahman (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to develop an Inclusive Economic Education Program based on Sustainable Management to improve the financial resilience of urban families in Makassar. The research method uses a quantitative approach with a pre-test and post-test design, involving target families who participate in training and mentoring programs. The results show a significant improvement in financial literacy and behavior, including understanding needs and wants, budgeting, saving habits, utilization of formal financial services, and adoption of fintech. These findings imply that similar programs are worth replicating to strengthen the economic resilience of families in urban areas in a sustainable manner.